Pemilihan Karir Perempuan Sebagai Akuntan Pendidik Dalam Perspektif Simone de Beauvoir: Studi Kasus pada Akuntan Pendidik Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tanjungpura Pontianak - Soraya, Soraya; Farizi, Zulham Al (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
Educators accountants have a significant role in the education world. This paper aims to gain a better understanding and in-depth information on the aspects that make up the women